2012
DOI: 10.4049/jimmunol.1200458
|View full text |Cite
|
Sign up to set email alerts
|

Virologically Suppressed HIV Patients Show Activation of NK Cells and Persistent Innate Immune Activation

Abstract: FcRγ is an ITAM-containing adaptor required for CD16 signaling and function in NK cells. We have previously shown that NK cells from HIV patients receiving combination antiretroviral therapy (cART) have decreased FcRγ expression, but the factors causing this are unknown. We conducted a cross-sectional study of cART-naive viremic patients (ART−), virologically suppressed patients receiving cART (ART+), and HIV-uninfected controls. CD8+ T cells were activated, as assessed by CD38+HLA-DR+ expression, in ART− pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
106
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 36 publications
(42 reference statements)
13
106
1
1
Order By: Relevance
“…Chronic HIV infection that induces ongoing activation of NK cells due to ADCC would be expected to elicit in vivo phenotypic and functional changes in NK cells similar to those observed after in vitro activation (i.e., reduced CD16 expression, hyporesponsiveness, and reduced NKp46 expression) (26)(27)(28)(29)39). Indeed, HIV infection results in a set of dysfunctional NK cell changes similar to that observed after CD16-mediated activation in vitro (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Thus, we speculate that continued activation of NK cells as a result of ADCC during untreated chronic viral infections could explain the reduced functionality of NK cells observed during HIV infection.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Chronic HIV infection that induces ongoing activation of NK cells due to ADCC would be expected to elicit in vivo phenotypic and functional changes in NK cells similar to those observed after in vitro activation (i.e., reduced CD16 expression, hyporesponsiveness, and reduced NKp46 expression) (26)(27)(28)(29)39). Indeed, HIV infection results in a set of dysfunctional NK cell changes similar to that observed after CD16-mediated activation in vitro (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Thus, we speculate that continued activation of NK cells as a result of ADCC during untreated chronic viral infections could explain the reduced functionality of NK cells observed during HIV infection.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, several studies (11,14,17,22) reported decreased NK cell-mediated ADCC by HIV-infected patients. Lastly, HIV infection is associated with a decreased expression of the activating natural cytotoxicity receptors (e.g., NKp30, NKp44, NKp46) and CD16, as well as an increased expression of inhibitory killer cell Iglike receptors (KIRs) (13,(15)(16)(17)(18)(19)(20). Alterations in the expression of these receptors likely have a significant negative impact upon the ability to respond to infections and malignant conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple reports define ongoing chronic inflammation and immune activation in HIV-infected patients, even in those with well-controlled viremia (22)(23)(24). Elevated levels of IL-6, tumor necrosis factor alpha (TNF-␣), and IL-1␣/␤ largely hallmark these events.…”
Section: Discussionmentioning
confidence: 99%